THE INFLUENCE OF VISIBILITY, CREDIBILITY, ATTRACTION AND POWER ON PURCHASE DECISION OF THE TYPE C15 SMARTPHONE REALME IN PONTIANAK CITY - Rizky Ramadhan, Rizky Ramadhan B1021161121 (Jurnal Manajemen Update, 2020)
ABSTRACTToday, many companies use strategies to deal with competition by marketing through promotion, especially through advertising. In order for the delivery of messages through advertisements to be accepted by consumers, there is a need for media as a tool, such as print media, radio, television, internet to social media so that it makes it easier for companies to convey messages and can be accepted by consumers well, with the help of appropriate communicators, namely celebrity endorsers as the medium for delivering messages from the product. The use of celebrity supporters who are currently popular as communicators is the main choice in advertising to influence people to make purchasing decisions. This study aims to test whether visibility, credibility, attraction and power have an effect on the decision to purchase a smartphone Realme type C15 in Pontianak City. The population in this study is the public (consumers) who have seen the Realme type C15 smartphone advertisement in Pontianak City, while the sample used is 100 respondents with purposive sampling technique. Collecting data in this study using an online questionnaire filled out by parties who meet the requirements. The questionnaire has been tested and has met the validity and reliability requirements. Data analysis using multiple linear regression and hypothesis testing. The results of multiple linear regression analysis and hypothesis testing show that the variables visibility, credibility, attraction and power have a positive and significant effect on purchasing decisions.Keywords: Visibility, Credibility, Attraction, Power and Purchase DecisionDAFTAR PUSTAKAAbdianur, A., & Sukimin, S. (2018). Celebrity Endorser (Bintang Iklan) Sebagai Komunikasi Pemasaran Terhadap Keputusan Membeli Oli Fastron Di Kota Balikpapan. Jurnal GeoEkonomiISSN-Electronic (e): 2503-4790, 5-28.Â Adisasmita, R. (2013). Teori-Teori Pembangunan Ekonomi Pertumbuhan Ekonomi dan Pertumbuhan Wilayah. Yogyakarta: Graha Ilmu.Â Anwar, S. (2011). Metode Penelitian Bisnis, Salemba Empat, JakartaÂ Ariani, Y.P. (2010). Analisis Pengaruh Pandangan Iklan, Kredibilitas Iklan, Daya Tarik Iklan dan Kekuatan Iklan terhadap Minat Beli (Studi Kasus Terhadap Pengguna Sepeda Motor Matic Merek Honda Vario di Kota Semarang). Skripsi. Semarang: Fakultas Ekonomi Universitas Diponegoro Semarang.Â Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta.Â Azwar, S. (2008). Penyusunan Skala Psikologi. Yogyakarta: Pustaka PelajarÂ Batra, R., et al. (1996). Advertising Management, 5th edition. New Jersey: Prentice Hall International edition.Â Belch., et al. (2009). Advertising and Promotion: an Integrated Marketing Comunication Prerspective (8th ed). New York: Mc Graw-Hill.Â BukaReview, (30 Juli 2020), Spesifikasi dan Harga Realme C15, HP Rp2 Jutaan dengan Baterai Jumbo. darihttps://review.bukalapak.com/gadget/spesifikasi-harga-realme-c15-112493Â Fildzah, N.A., & Sari.D. (2017). Pengaruh Celebrity Endorser dan Word Of Mouth Terhadap Keputusan Pembelian Produk Swater Online Shop Alco Di Media Sosial Instagram. Ekonomi, Bisnis & Entrepreneurship, 2(11), 99-112.Â Ghozali, I. (2013). â€œAplikasi Analisis Multivariate dengan Program IBM SPSS 21â€. Semarang: Badan Penerbit Universitas Diponegoro.Â Hartono. (2004). Statistik untuk Penelitian. Yogyakarta: Pustaka Pelajar.Â Ifeanichukwu, C. D (2016). Effect of Celebrity Endorsements on Consumers Purchase Decision in Nigeria. International Research Journal of Management, IT & Social Science, 9(3), 120-128.Â Â Kerlinger, F. N. (1973). Founding Of Behavior Research, Holt. New York: Rinchart and Winston Inc.Â KliknKlik, Pengertian Smartphone, diakses (2009), PT Portal Biz Nusantara darihttps://kliknklik.com/content/66-pengertian-smartphoneÂ Kotler, P. (2005). Manajemen Pemasaran. Jilid 1 dan 2. Jakarta: PT Indeks Kelompok Gramedia.Â Kotler, P., & Keller, K.L. (2012). Manajemen Pemasaran Jilid I Edisi ke 12. Jakarta: Erlangga.Â Kotler, P., & Amstrong, G. (2012). Principles of Marketing. New Jersey: Prentice-Hall, Inc.Â Lombo, V.E.P., & Tielung, M.V.J. (2014). The Impact of Celebrity Endorsementto Youth Consumer Purchase Decision on Adidas Apparel Product. EMBA, 3(2), 1246-1254.Â McCracken, G. (1989). Who Is the Celebrity Endorser? Cultural Foundations of the Endorsement Process. Journal of Consumer Research, (16), 310-32.Â Muslim, I.S. (2012). Pengaruh Dimensi Celebrity Endorser terhadap Citra Merek (Studi pada Iklan Mie Sedaap Versi Edwin Lau pada Mahasiswa Ilmu Rumpun Kesehatan Universitas Indonesia). Skripsi. Depok: Fakultas Ilmu Sosial Dan Ilmu Politik, Departemen Ilmu Administrasi, Program Sarjana Reguler, Program Studi Ilmu Administrasi Niaga, Universitas Indonesia.Â Nugroho, J. S. (2003). Perilaku Konsumen Konsep dan Implikasi untuk Strategi dan Penelitian Pemasaran. Jakarta: Kencana.Â Oktafiani, R., & Silaningsih, E. (2015). Pengaruh Celebrity Endorser Terhadap Keputusan Pembelian Kartu Perdana XL Di Kota Bogor. Jurnal Visionida, 2(1), 45-58.Â Percy, L., & Rosenbaum, R. (2012). Strategic Advertising Management (4th ed.). England: Oxford University Press.Â Priyatno, D. (2012). Belajar Cepat Olah Data Statistik Dengan SPSS. Yogjakarta: Andi Offset.Â Priyono. (2016). Metode Penelitian Kuantitatif. Sidoarjo: Zifatama Publishing.Â Rossiter, John R. & Larry Percy (1997), Advertising Communications and PromotionManagement, Boston, MA: McGraw-Hill, second edition. Rossister, J. R., & Percy, L. (1997). Advertising Communication and Promotion Management. Boston: McGraw-Hill, Second edition.Â Rossister, J.R., & Percy, L. (1985). Advertising Communication Models. Advances in Consumer Research, (12), 510-524.Â Royan, F.M. (2004). Marketing Celebrities: Selebriti dalam Iklan dan Strategi Selebriti Memasarkan Diri Sendiri. Jakarta: PT. Elex Media Komputindo.Â Royan, F.M. (2005). Sales Force (Meningkatkan Penjualan Dengan Rancangan Bangun Sales Force Effective). Yogyakarta: Penerbit Andi.Â Santoso, S. (2012). Statistic Parametic. Jakarta: PT Gramedia Pustaka UmumÂ Schiffman, L & Kanuk, L.L. (2007). Consumer Behaviour 7 th. Edition. (Perilaku Konsumen). Jakarta: PT. Indeks.Â Selular.id, (19 Mei 2020), IDC: Top 5 Brand Smartphone di Indonesia Q1-2020 dari https://selular.id/2020/05/idc-top-5-brand-smartphone-di-indonesia-q1-2020/Â Â Sekaran, U., & Roger B. (2017). Metode Penelitian untuk Bisnis: Pendekatan Pengembangan-Keahlian, Edisi 6, Buku 2. Jakarta: Salemba Empat.Â Shimp, Terence A. (2007). Advertising, Promotion, and Other Aspects of Integrated Marketing Communications. USA: Thomson Higher Education.Â Sukmawati, A., & Suyono, J. (2005). Analisis Pengaruh Karakteristik Bintang Idola Iklan (Celebrity Endorser) Terhadap Minat Beli Konsumen Sebuah Merek Multivitamin (studi kasus pada Mahasiswa Fakultas Ekonomi Universitas Sebelas Maret Surakarta). Fokus Manajerial, 1(3), 21-32.Â Sumarwan, U. (2003). Perilaku Konsumen: Teori dan Penerapannya dalam Pemasaran, Cetakan Pertama, Jakarta: Ghalia Indonesia.Â Sugiarto, Y.S. (2012). Pengaruh Celebrity Endorser terhadap Minat Beli Konsumen (Studi Kasus pada Produk Mie Sedap) Skripsi. Salatiga: Universitas Kristen Satya Wacana, Salatiga.Â Â Sugiyono. (2017). Metode Penelitian Bisnis Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R & D. Bandung: Alfabeta.Â Suryadi, D. 2006. Promosi Efektif Menggugah Minat dan Loyalitas Pelanggan. Yogyakarta: Tugu Publisher.Â Sutisna, (2003). Perilaku Konsumen dan Komunikasi Pemasaran, Cetakan Ketiga. Bandung: PT. Remaja Rosdakarya.Â Swastha, B. (2002). Manajemen Pemasaran. Edisi Kedua. Cetakan Kedelapan. Jakarta: Penerbit LibertyÂ Swastha, B., & Sukotjo, I. (2007). Pengantar Bisnis Modern edisi 3. Yogyakarta: Liberty Yogyakarta.Â Swastha, B. (2007). Manajemen Pemasaran Modern. Yogyakarta: Liberty Offset.Â Superwiratni (2018). Pengaruh Celebrity Endorsement Terhadap Keputusan Menginap Di Cottage Daarul Jannah. Toursim and Hospitality Essentials Journal, 2(8), 99-110.Â Tjondrokoesoemo, M. (2017). Celebrity Endorser Terhadap Keputusan Pembelian. Manajemen dan Star-Up Bisnis. 3(2), 287-295.Â Tjiptono, F. (2012). Pemasaran Jasa. Jogjakarta: Penerbit Andi.Â Tribun Jogja News, REALME C15 Kenalkan Syifa Hadju & Iqbaal Ramadhan sebagai Brand Ambassador, diakses (30 April 2020), dari https://jogja.tribunnews.com/2019/04/30/realme-3-pro-kenalkan-syifa-hadju-iqbaal-ramadhan-sebagai-brand-ambassadorÂ Ujang, S. (2004).Â Perilaku Konsumen Teori dan Penerapannya dalam Pemaasaran. Bogor: Ghalia Indonesia.Â Umar, H. (2013). Metode Penelitian untuk Skripsi dan Tesis. Jakarta: RajawaliÂ Warren, K. J., & Mark, G.C. (2017). Global Marketing. 9th Edition. Harlow: Pearson Education Limited.Â Wikipedia. Iqbaal Ramadhan - Wikipedia bahasa Indonesia. Diakses (8 September 2020), dari https://id.wikipedia.org/wiki/Iqbaal_RamadhanÂ Wikipedia. REALME â€“ Wikipedia Bahasa Indonesia. Diakses (25 Agustus 2020), dari https://id.wikipedia.org/wiki/RealmeÂ Â Yusiana, R., & Maulida, R. (2015). Pengaruh Gita Gutawa Sebagai Brand Ambassador Ponds Dalam Mempengaruhi Keputusan Pembelian (Studi Kasus Pada Mshasiswi Universitas Telkom Jurusan D3 MAnajemen Pemasaran). Ecodemica, 1(3), 311-316.Â Zahra, R.R., & Rina, N. (2018). Pengaruh Celebrity Endorser Hamidah Rachmayanti Terhadap Keputusan Pembelian Produk Online Shop Mayoutfit DI Kota Bandung. JURNAL LONTAR, 1(6), 43-53.